Establishment and Effectiveness Evaluation of a Scoring System-RAAS (RDW, AGE, APACHE II, SOFA) for Sepsis by a Retrospective Analysis - Huang Y; Jiang S; Li W; Fan Y; Leng Y; Gao C (Dove Medical Press, 2022)
Yingying Huang,1,* Shaowei Jiang,1,* Wenjie Li,1 Yiwen Fan,2 Yuxin Leng,3 Chengjin Gao1 1Emergency Department, Xinhua Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, Shanghai, People's Republic of China; 2Department of Pathology Medicine Biology, The University Medical Center Groningen, Groningen, the Netherlands; 3Critical Care Medicine Department, Peking University Third Hospital, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Chengjin Gao; Yuxin Leng Email gaochengjin@xinhuamed.com.cn; lengyx@bjmu.edu.cnBackground: A modified scoring system based on the RDW, AGE, SOFA, and APACHE II score (RAAS score) was composed to investigated the short-, medium-, and long-term high risk of mortality in patients with sepsis identified early in the emergency department (ED).Methods: Data were collected from a total of 1066 sepsis patients in emergency department, Xinhua Hospital Affiliated to Shanghai Jiao Tong University School of Medicine from March 2013 to April 2021, including 529 patients in the primary cohort and 537 patients in the validation cohort. By comparing each parameter and the area under ROC (AUC) and K-M (Kaplan-Meier) survival curve in different periods, valuable parameters were screened out to form a new scoring system, and finally the prediction model of the nomogram was built.Results: The RAAS scoring system, consisting of RDW, AGE, SOFA and APACHE II, is a 0- 6 scale to reflect the severity of sepsis. AUC at 30, 60, and 90 days was 0.816, 0.815, and 0.820, respectively. K-M curves across six prognostic time periods in both databases showed survival probabilities with different RDW segments and RAAS scores. In the calibration curve, the results of the internal validation of the primary cohort and the results of the external validation cohort showed the prognostic accuracy of RAAS.Conclusion: The RAAS score system is a novel and reliable indicator to predict the short-term and medium-term mortality of patients with sepsis. With the increase of the RAAS score, the mortality of patients with sepsis gradually increases.Keywords: sepsis, risk factors, prognosis, mortality, nomograms